Qualitätsmanagement: Kollegiales Peer-Review-Verfahren in der Intensivmedizin - Muhl, Elke (DMW - Deutsche Medizinische Wochenschrift, 2018)
We report on the German Peer Review procedure for the quality management of Intensive Care Wards. The third up-date of the quality-indicators was published in 2017. The Peer Review Procedure, its organization, the development of quality indicators in Germany and their benefit for the patients is introduced.
Keywords: Peer-Review; Intensivmedizin; Qualitätsindikatoren